Kampung Muram Sari sebagai Basis Pengembangan Ternak Kambing di Kabupaten Merauke - Abdul Rizal; David Laiyan; Yosehi Mekiuw; Adrianus Adrianus; Mani Yusuf; Anwar Anwar (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
Muram Sari Village is one of the villages in the Semangga District, Merauke Regency with the largest population in the Semangga District. This village is dominated by transmigration communities who in fact have a livelihood as farmers and ranchers. One of the livestock developed is goat which is considered to be able to help boost the economy of farmers from generation to generation. Goat farming is currently being cultivated by breeders, although its implementation has not been fully maximized. This is due to the lack of understanding of breeders on the development of goats, the maintenance system is still traditional and the maintenance management and group management are not optimal. Therefore, with the Community Partnership Service (PKM) activity, the implementing team will provide full participation in solving problems faced by the group, especially cultivation management, housing systems, group management, and processing of sewage waste as organic fertilizer. It is hoped that in the future, Muram Sari Village will become the basis for developing goats in Merauke Regency.